Interface coupling model of Stefan phase change during thermal dissociation of natural gas hydrate. (August 2021) - Li, Mingchuan; Fan, Shuanshi; Xu, Fuhai
Highlights: Coupling Stefan model was built for a discontinuous hydrate body. A Neumann solution was obtained using Boltzmann similar variables. The uniqueness of solution was determined by monotonicity proving. Abstract: The thermal dissociation process that occurs in a natural gas hydrate is a Stefan phase-change problem with moving boundaries. Based on the integral form of a heat conduction model, for a continuous single-phase hydrate control volume, the energy conservation condition for interfacial coupling during the Stefan phase-change was built for the control volume of thermal dissociation of a natural gas hydrate with a sharp moving boundary. A Neumann solution of the Stefan phase-change model was obtained for the thermal dissociation in a semi-infinite natural gas hydrate reservoir, using Boltzmann similar variables. A unique solution for the Stefan model was found using a monotonic of the transcendental equation. An example analysis was used to verify, the monotonicity of the transcendental equation, and uniqueness of the solution of the Stefan model. The MATLAB program was used to study, the laws of temperature distribution, and dissociation frontal brim during the thermal dissociation process in a hydrate reservoir. Sensitivity fitting studies showed that, the solution of transcendental equation and interface position gradually increased, whereas, the depth penetrated and time penetrated gradually decreases with increasing temperature.